PERAN POLITIK KYAI DI KABUPATEN REMBANG DALAM PEMILU TAHUN 1994-2009 (Jurusan Sejarah Fakultas Ilmu Sosial Universitas Negeri Semarang, 2012)
The problems studied in this research is How the political role of clerics in the form of Rembang. How is the interaction between the government and the clerics with political figures. How is the role of clerics in influencing public policy preferences in the general election. Location of the study is the Apex District from 1994 to 2009 time frame. The research method used is the historical results of this study found at least two political streams clerics, religious scholars as an actor first and clerics as a participant . Conclusions drawn from this research that the role of clerics as community leaders not only have the